2018
DOI: 10.14505//jemt.v9.1(25).25
|View full text |Cite
|
Sign up to set email alerts
|

Coopetitive Games for Sustainability of Global Feeding and Climate Change: Recent Developments

Abstract: In this paper, we face the problem of global feeding sustainability and related environmental issues, with a strong attention to possible public heath improvements. In particular, we consider food producers and sellers of vegan (or vegetarian) and non-vegan (or non-vegetarian) food and we build up feasible and measurable contracts between two different food producers, in order to construct a more sustainable and healthier diet for future generations. At this aim, we use co-opetitive approach by means of game t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We found that customers recognized green practices and shared their perceptions in UGC, but their perceptions were limited to food-related green practices, such as the use of local/organic ingredients and vegan menus. A vegan diet has become a sustainability trend to lessen the harmful ecological impact of meat production due to the heavy use of natural resources required for meat production and massive emissions of greenhouse gasses [63]. Also, many environmentally conscious customers prefer to consume local and organic food products, which reduce food miles and the use of chemicals [64].…”
Section: Discussionmentioning
confidence: 99%
“…We found that customers recognized green practices and shared their perceptions in UGC, but their perceptions were limited to food-related green practices, such as the use of local/organic ingredients and vegan menus. A vegan diet has become a sustainability trend to lessen the harmful ecological impact of meat production due to the heavy use of natural resources required for meat production and massive emissions of greenhouse gasses [63]. Also, many environmentally conscious customers prefer to consume local and organic food products, which reduce food miles and the use of chemicals [64].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these problems can, in part, be mitigated with a more sustainable food diet by eating less meat; see [16,17]. Some resources can be preserved by investing in the development of sustainable machinery with low CO 2 emissions or machinery that allow the reuse or recycling of natural resources.…”
Section: Possible Actions For Mitigating Global Food Scarcitymentioning
confidence: 99%
“…Therefore, our approach could be considered significantly new because, on the one hand, we use infinite non-cooperative games for the determination of equilibria and Pareto boundaries in a possible realistic competitive interaction outside the eco-industrial park; on the other hand, we introduce a collaborative dynamics to find efficient policies for the expansion of the eco-industrial park and for the improvement of its facilities as well as the environmental protection and respect for public health. Other studies in which the authors have used this new approach applied to different environmental contexts are [15][16][17][18][19].…”
Section: Novelty Of the Approach In An Industrial Symbiosis Contextmentioning
confidence: 99%